What are the barriers and facilitators to self-management of chronic conditions reported by women? A systematic review - Dawn Dowding; Rohna Kearney; Lucy Dwyer (BMJ Open)
Introduction Pelvic organ prolapse (POP) can be effectively managed using a pessary. A scoping review found that pessary self-management appears to benefit women with no increased risk. Despite this, many are unwilling to self-manage their pessary. At present, there is a lack of understanding about what affects willingness to self-manage a pessary. However, there may be relevant, transferable findings from other literature about barriers to the self-management of other chronic conditions. Therefore, this systematic review aims to identify, appraise and synthesise the findings of published qualitative research exploring the barriers and facilitators to self-management of chronic conditions reported by women.Methods and analysis The systematic review will be conducted and reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and a guide for the systematic review of qualitative data. A search of MEDLINE, CINAHL, Embase and PsycInfo will be undertaken to identify relevant articles that meet the eligibility criteria using the search terms ‘Women’, ‘Woman’ ‘Female,’ ‘Chronic’, ‘Long-term’, ‘Disease’, ‘Illness’, ‘Condition’ ‘Health,’ ‘Self-management,’ ‘Qualitative,’ ‘Barrier’ and ‘Facilitator’. A hand search of the reference list of non-original research identified during the search but excluded will be conducted for additional publications, which meet the inclusion and exclusion criteria. Studies published before 2005 and those not available in English will be excluded. Data relevant to the topic will be extracted and critical appraisal of all included publications undertaken.Ethics and dissemination No ethical or Health Research Authority approval is required to undertake the systematic review. The systematic review findings will be disseminated by publication. The findings will also inform subsequent exploratory work regarding pessary self-management.PROSPERO registration number CRD42022327643.